YOGA, BREATHWORK, AND VOCAL PERFORMANCE ENHANCEMENT - Ghorpade, Vasundhara V; Swamikannu, Bhuminathan; Chaitali; Wawage, Pawan; Patil, Balkrishna K; Patkar, Uday Chandrakant (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Vocal performance requires a harmonious integration of breath control, posture, mental focus, and vocal endurance. In recent years, holistic practices such as yoga and breathwork have gained attention for their potential to enhance vocal capabilities among singers and performers. This study explores the role of yoga postures (asanas) and controlled breathing techniques (pranayama) in improving vocal performance, respiratory efficiency, and vocal stability. Yoga practices contribute to better posture, enhanced lung capacity, and reduced muscular tension, all of which are essential for optimal voice production. Breathwork techniques help regulate airflow, strengthen respiratory muscles, and improve breath support during singing or speech. Additionally, yoga promotes mental relaxation and stress reduction, which can positively influence vocal confidence and stage performance. The research analyzes how integrating structured yoga routines and breathing exercises into vocal training programs can support improved pitch control, vocal stamina, and sound resonance. The study also highlights the physiological and psychological benefits of these practices for professional singers, public speakers, and performing artists. By examining existing literature and practical training approaches, this paper demonstrates that yoga and breathwork can serve as effective complementary techniques for vocal training. The findings suggest that incorporating mind–body practices into vocal education may significantly enhance vocal quality, endurance, and overall performance outcomes.